Isolation, structure, biological characterization, and synthesis of beta-[Tyr9]melanotropin-(9-18) decapeptide from pig hypothalami. - Schally, A V (1980)
A decapeptide with the amino acid sequence H-Tyr-Phe-Arg-Trp-Gly-Ser-Pro-Pro-Lys-Asp-OH was isolated from acid extracts of porcine hypothalami, structurally and biologically characterized, and synthesized. Except for the NH2-terminal tyrosine, this decapeptide corresponds to the amino acid sequences 9-18 of porcine beta-melanotropin (beta-MSH) and 49-58 of porcine beta-lipotropin (beta-LPH); it also has a tetrapeptide sequence of amino acids (Phe-Arg-Trp-Gly) common to the 7-10 sequences in corticotropin (ACTH) and alpha-MSH. beta-MSH, beta-LPH, alphaMSH, and ACTH from various species all have a histidine residue in the position immediately preceding the common sequence, and the occurrence of a natural peptide with the tyrosine residue in the corresponding site has not been previously reported. This suggests that the beta-[Tyr9]MSH-(9-18) decapeptide might be a fragment of a still larger precursor (prohormone) possibly related to beta-LPH.